Climate Wars : The Fight for Survival as the World Overheats - Dyer, Gwynne (Oxford, England One World, 2011)
"The Intergovernmental Panel on Climate Change predicts that the average global temperature will rise between 2 degrees and 6.4 degrees Celsius by the end of this century. These are conservative estimates, based on a lowest-common-denominator consensus among scientists and further watered down by governments. They make no allowance for feedback phenomena and potential runaway heating. But a World Bank study in India last year suggested that even 2 degrees hotter means a 25 percent cut in Indian food production. The core problem with climate changes is not sea level rise or bio-diversity; it is food supply"--Provided by publisher
Include Reference and Index
Keywords: Security, International -- Environmental degradation--Political aspects -- Geophysics -- Climatic changes--Political aspects -- Global warming--Political aspects